2021
DOI: 10.1038/s41598-021-92547-8
|View full text |Cite
|
Sign up to set email alerts
|

A gain-of-function NLRP3 3′-UTR polymorphism causes miR-146a-mediated suppression of NLRP3 expression and confers protection against sepsis progression

Abstract: Nucleotide-binding domain and leucine-rich repeat (LRR)-containing family protein 3 (NLRP3) regulated the maturation of inflammation-related cytokines by forming NLRP3 inflammasome, which plays pivotal roles in sepsis pathogenesis. In this study, we evaluated the genetic association of NLRP3 polymorphisms with sepsis (640 patients and 769 controls) and characterized the impact of NLRP3 polymorphisms on NLRP3 expression and inflammatory responses. No significant differences were observed in genotype/allelic fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Two C5 genetic SNPs, rs17611 and rs2269067, were genotyped with an iMLDRTM multiple SNP typing kit (Shanghai Tianhao Biotechnology Co., Ltd.), according to our previous studies. 5 In addition, 10% of the samples were randomly selected as an independent validation group for regenotyping to monitor genotyping quality. Final analysis of the experimental data was performed on GeneMapper 4.1 (Applied Biosystems, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two C5 genetic SNPs, rs17611 and rs2269067, were genotyped with an iMLDRTM multiple SNP typing kit (Shanghai Tianhao Biotechnology Co., Ltd.), according to our previous studies. 5 In addition, 10% of the samples were randomly selected as an independent validation group for regenotyping to monitor genotyping quality. Final analysis of the experimental data was performed on GeneMapper 4.1 (Applied Biosystems, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…30 Healthy controls and patients with sepsis were excluded if they met the exclusion criteria described in our previous studies. [5][6][7] Two milliliters of peripheral venous blood from the enrolled subjects was collected into an ethylene-diamine tetraacetic acid-containing tube for SNP genotyping within the first 12 h of sepsis diagnosis. Peripheral blood mononuclear cells (PBMCs) and plasma were extracted from the peripheral venous blood and stored separately at −80 °C until analysis.…”
Section: Subject Enrollmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, NLRP3 can be activated by common culprit Gram-positive and Gram-negative bacteria found in septic patients such as Staphylococcus aureus and Streptococcus pneumoniae [46][47][48]. Interestingly, polymorphisms of the NLPR3 gene have been demonstrated to impart gain-offunction that resulted in a suppression of NLRP3 expression and downstream inflammatory activation, which resulted in protection of patients from progression of sepsis [49].…”
Section: Progressing Beyond Associationsmentioning
confidence: 99%
“…Interestingly, a recent study showed that the G/G genotype of rs10754558 was significantly associated with increased risk of developing septic shock compared to the controls, and mechanistic studies utilizing luciferase reporter vectors containing NLRP3 3′-UTR with the rs10754558 variation showed that the allele C had a higher affinity to miR-146a, a negative regulator of NLRP3 transcripts and, consequently, the allele C of rs10754558 was more sensitive to the suppressive effects of miR-146a than the allele G [75]. These results further validated the functional relevance of rs10754558 and established the molecular bases by which a genetic variant in the 3′-UTR of the NLRP3 gene regulates NLRP3 expression, where a gain-of-function alteration (allele G) augments the resistance of NLRP3 transcripts to the suppressive regulatory effects of miR-146a-5p (Figure 2).…”
Section: The Effects In Polymorphisms In Nlrp3 Expression and Functionmentioning
confidence: 99%